2018
DOI: 10.1007/s00259-018-4238-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual-phase [18F]florbetapir in frontotemporal dementia

Abstract: PurposeThe PET tracer [18F]florbetapir is a specific fibrillar amyloid-beta (Aβ) biomarker. During the late scan phase (> 40 min), it provides pathological information about Aβ status. Early scan phase (0–10 min) can provide FDG-‘like’ information. The current investigation tested the feasibility of using florbetapir as a dual-phase biomarker in behavioural variant frontotemporal dementia (bvFTD).MethodsEight bvFTD patients underwent [18F]florbetapir and [18]FDG-PET scans. Additionally, ten healthy controls an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
5
18
0
Order By: Relevance
“…Previous rCBF dynamic PET studies with inclusion of bvFTD patients showed a good correlation between rCBF and FDG-PET hypometabolism patterns. 46 Compared to controls, low rCBF in the ACC, lateral temporal and frontal lobe in the symptomatic P301L patient is largely in correspondence with a previous SPECT study in symptomatic MAPT mutation carriers. 22 Interestingly, borderline abnormal low ACC rCBF compared to controls was found in one presymptomatic P301L mutation carrier, confirming the results of a previous study that found glucose hypometabolism in the anterior cingulate of presymptomatic P301L carriers.…”
Section: Discussionsupporting
confidence: 85%
“…Previous rCBF dynamic PET studies with inclusion of bvFTD patients showed a good correlation between rCBF and FDG-PET hypometabolism patterns. 46 Compared to controls, low rCBF in the ACC, lateral temporal and frontal lobe in the symptomatic P301L patient is largely in correspondence with a previous SPECT study in symptomatic MAPT mutation carriers. 22 Interestingly, borderline abnormal low ACC rCBF compared to controls was found in one presymptomatic P301L mutation carrier, confirming the results of a previous study that found glucose hypometabolism in the anterior cingulate of presymptomatic P301L carriers.…”
Section: Discussionsupporting
confidence: 85%
“…Within-subject correlations of eAV45 and [ 18 F]FDG PET distributions were globally high and similar to published studies ( Asghar et al, 2018 , Fu et al, 2014 , Hsiao et al, 2012 , Joseph-Mathurin et al, 2018 , Ottoy et al, 2019 , Rodriguez-Vieitez et al, 2016 , Rostomian et al, 2011 ), and generally associated with middle-to-high vertex-wise inter-subject correlations between both modalities irrespective of the reference region. Higher correlations in vulnerable regions in AD may be explained by a greater dynamic range of metabolism and perfusion within these regions due to our mixed study population ranging from healthy controls to Alzheimer’s clinical syndrome with MCI or dementia.…”
Section: Discussionsupporting
confidence: 88%
“…Validating the results on a mixed study population provides further support that optimal early time frame and preprocessing methods of eAV45 are not dependent on clinical diagnosis, suggesting wider applicability of our methodology. While previous studies ( Asghar et al, 2018 , Hsiao et al, 2012 , Kuo et al, 2017 , Lin et al, 2016 , Ottoy et al, 2019 ) chose the optimal early time frame of eAV45 based solely on the best within- or inter-subject correlation with [ 18 F]FDG PET SUVR values, this study considers for the first time many complementary quantitative analyses to robustly optimize both the early time frame and the preprocessing methods of eAV45, by comprehensively assessing the similarities and differences between eAV45 and [ 18 F]FDG PET. Moreover, this study contrasted the discriminatory power of eAV45 and [ 18 F]FDG PET in individual cases using (i) a robust cross-validation scheme to avoid overly optimistic classification performance and (ii) a whole-brain data-driven approach rather than specific ROIs to better compare performance between both modalities.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, amyloid PET is an important potential biomarker for differential diagnosis of AD from FTLD [49], and for studying the clinicopathological correlation of amyloid pathology in FTLD [50]. Since recent tau PET tracers have off-target problems involving binding to non-specific tau molecules, tau PET does not indicate pure tau deposition, but rather is used to show non-tau associated with neurodegeneration pathology [51,52] and the correlation of FTLD pathology with function [53]. PNFA may be associated with Fig.…”
Section: Amyloid Imaging and Tau Imaging In Ftldmentioning
confidence: 99%